MEMBANGUN ECOLOGICAL CITIZENSHIP MELALUI CIVIC EDUPRENEURSHIP: TRANSFORMASI LIMBAH PROGRAM MAKAN BERGIZI GRATIS MENJADI ECO ENZYME SEBAGAI PRAKTIK KEWARGANEGARAAN BERKELANJUTAN DI SMP NEGERI 2 NGANTANG - Adi Kurniawan, Prima; Febriana Umbas, Reri; Lailatus Mauludiyah, Siti; Nanik Setyowati, Rr; Maizul Habibah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Free Nutritious Meal Program provides benefits in meeting students’ nutritional needs, but it also has the potential to generate food waste that impacts the school environment. This study aims to analyze the process of transforming MBG waste into Eco Enzyme as a practice of Civic Edupreneurship in fostering ecological citizenship at SMP Negeri 2 Ngantang. The study employs a descriptive qualitative approach, with research subjects including the school principal, the Adiwiyata Team, the Malang Regency Environmental Agency Team, and students. Data were collected through participatory observation, in-depth interviews, Focus Group Discussions (FGDs), and documentation. Data analysis utilized the interactive model by Miles, Huberman, and Saldana, which encompasses data collection, data presentation, and drawing conclusions. The research results indicate that the Eco Enzyme program successfully transformed MBG organic waste into useful products through the processes of collection, sorting, fermentation, and utilization of the fermentation products. The program’s success was supported by collaboration among the school principal, the Adiwiyata Team, students, and the Malang Regency Environmental Agency. This program can reduce the volume of food waste from 5–10 kg to 1–4 kg per day from school food waste. In addition to producing liquid organic fertilizer and compost that benefit the school environment, this program successfully fosters values of ecological citizenship, including ecological responsibility, mutual cooperation, environmental awareness, and a focus on sustainable solutions. Research findings indicate that the transformation of food waste into Eco Enzyme serves as an effective model of environmental citizenship education in shaping students’ character while simultaneously supporting sustainable waste management.